Instructional design of online courses in Mozambique - Franco, David (2022)
The potential of electronic books (ebooks) has been discussed widely, due mainly to their role in helping the user transform passive reading into interactive and dynamic learning, while promoting better retention and appropriation of materials. Taking this premise, the present study follows an exploratory and qualitative approach, discussing how the use of ebooks can improve learning, motivation, dynamism and interactivity in Distance Education. This study was supported by a bibliographic review and a survey method through an online questionnaire used as data collection instruments. The sample consisted of students who attended distance courses taught by the Open University ISCED – UnISCED in Mozambique. The scientific literature studied, and the results from the field research, show the practicality of using ebook as a learning resource and they facility the interactivity.